THE STUDY "REGISTER OF PATIENTS AFTER ACUTE STROKE (REGION)". PART 2. OUTPATIENT PROSPECTIVE REGISTER OF PATIENTS AFTER ACUTE STROKE (ACCORDING TO THE RESULTS OF THE PILOT PHASE OF THE STUDY) - S. А. Boytsov; M. M. Loukianov; S. S. Yakushin; S. Yu. Martsevich; L. V. Stakhovskaya; A. N. Vorobyev; A. V. Zagrebelnyy; N. P. Kutishenko; A. N. Kozminsky; K. A. Moseichuk; K. G. Pereverzeva; E. A. Pravkina; et al. (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study particularities of course and outcomes of acute cerebrovascular accident (ACVA), quality of examination and medical treatment within a framework of an outpatient register.Material and methods. Two outpatient registries were organized on the base of one of Ryazan outpatient clinics within a framework of the pilot phase of the REGION study: the register of patients who had experienced ACVA of any remoteness (ACVA-AR register, n=200) and the register of patients who had visited the outpatient clinic for the first time after cerebral stroke (ACVA-FV register, n=115). Particularities of ACVA development, concomitant cardiovascular diseases (CVD) and noncardiac diseases were analyzed. We estimated accordance of methods of examination and prescribed medical treatment with clinical guidelines. Long-term outcomes were also evaluated in the course of prospective follow-up.Results. Patients of both  registers had  concomitant CVD (on an average 3 diagnosis) and  noncardiac comorbidity (on an average 1 diagnosis). Majority of patients at the outpatient phase  received inadequate treatment for cardiovascular risk decrease, especially before  reference ACVA. The ACVA-FV register patients as compared to the ACVA-AR ones (who had experienced ACVA on an average 4.8 years earlier) were more often (p<0.05) examined by instrumental and laboratory methods of diagnostics during the post-stroke follow-up in outpatient settings. ACVA-FV register patients as compared to the ACVA-AR ones were also more often (p˂0.05) prescribed prognosis-modifying therapy (statins – 46.9% vs 11%, acetylsalicylic acid – 54.8% vs 28%, ACE inhibitors – 46.1% vs 29%, and anticoagulants in atrial fibrillation – 17.6% vs 2.3%, respectively). Mortality rates in the ACVA-AR and ACVA-FV registers for 2 years were 15.5% and 32.2%, respectively (p=0.005), incidence rates of myocardial infarction – 2.5% and 0%, respectively (p=0.09), recurrent ACVA – 14.5% and 11.3%, respectively, (p=0.42).Conclusion. Examination and medical treatment of the patients in the outpatient clinic were suboptimal especially before  ACVA development. However examination and treatment quality had improved significantly (although insufficiently) during 5-year time span between ACVA development in the ACVA-AR and ACVA-FV registers. High mortality rate (22.7%) in the first 3 months of outpatient follow-up after ACVA is an unsolved challenge.